2006
DOI: 10.1111/j.1440-1681.2006.04352.x
|View full text |Cite
|
Sign up to set email alerts
|

ROLE OF CAPSAICIN‐SENSITIVE SENSORY NERVES IN MEDIATION OF THE CARDIOVASCULAR EFFECTS OF THE ESSENTIAL OIL OF CROTON ZEHNTNERI LEAVES IN ANAESTHETIZED RATS

Abstract: The essential oil of Croton zehntneri Pax et Hoffm. (EOCZ) contains anethole (42%) and estragole (46%), two isomers that share some chemical structural similarities with capsaicin. The present study investigated the cardiovascular effects of EOCZ and the role of capsaicin-sensitive sensory nerve fibres in the mediation of these effects in anaesthetized rats. 2. Intravenous bolus injection of EOCZ (1-20 mg/kg) elicited dose-dependent hypotension and bradycardia that were immediate and transient. Similar respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 40 publications
1
19
0
3
Order By: Relevance
“…In four different groups of rats, maximal changes in MAP and HR elicited by i.v. injection of EOAC and NP (both at 10 mg/kg) were determined before and 20 min after a cervical bilateral vagotomy (Series 2; n = 5 and 6, respectively), before and 20 min after bilateral perineural treatment (PNT) with CAP (250 μg/mL; n = 5 and 6, respectively) (Series 3) as previously described [11], before and 2 min after i.v. pretreatment with the competitive TPRV 1 receptor antagonist, capsazepine (1 mg/kg) [12] ( n = 6 and 6, respectively) (Series 4), and before and 5 min after i.v.…”
Section: Methodsmentioning
confidence: 99%
“…In four different groups of rats, maximal changes in MAP and HR elicited by i.v. injection of EOAC and NP (both at 10 mg/kg) were determined before and 20 min after a cervical bilateral vagotomy (Series 2; n = 5 and 6, respectively), before and 20 min after bilateral perineural treatment (PNT) with CAP (250 μg/mL; n = 5 and 6, respectively) (Series 3) as previously described [11], before and 2 min after i.v. pretreatment with the competitive TPRV 1 receptor antagonist, capsazepine (1 mg/kg) [12] ( n = 6 and 6, respectively) (Series 4), and before and 5 min after i.v.…”
Section: Methodsmentioning
confidence: 99%
“…Previously, we reported that EOCA was able to relax both a conduit artery and a resistance vascular bed preparation [8], an effect that could be responsible for a putative hypotensive action of this essential oil, as previously demonstrated for EOCN [9] and EOCZ [13, 14] in normotensive rats. As no information in the international literature is available regarding this hypothesis, the present study was undertaken to test such a possibility and also to elucidate the mechanisms underlying the vasorelaxant effects of EOCA.…”
Section: Introductionmentioning
confidence: 74%
“…Doses of antagonists and EOCA were chosen according to those recommended in the literature and those employed in our previous investigations [13, 14, 18, 2023], respectively. In a first series of experiments, a dose-effect relationship was determined in anesthetized rats which have been submitted ( n = 6) or not ( n = 5) to a cervical bilateral vagotomy.…”
Section: Methodsmentioning
confidence: 99%
“…vagus reflex) and then an increase in blood pressure. Further studies carried out in anesthetized rats showed that EOCZ‐induced capsaicin‐like bradycardic and depressor reflex is mediated through the activation of vanilloid TPRV 1 receptors located on sensory vagal nerves [9]. A hydrolate obtained from stalk and leaves of C. zehntneri contains compounds with larvicidal activity against third instar Aedes aegypti larvae [10], and EOCZ presents antifungal activity against the dermatophytic fungus Microsporum canis [11].…”
Section: Introductionmentioning
confidence: 99%